The Use Recycled Glass Waste in Geotechnical Road Courses - زربا غنوة (Latakia University Journal -Engineering Sciences Series, 2020)
The purpose of this research is to study the use of recycled glass in base courses- class3, in addition to environmental and economic benefits. Recycled Glass - Crushed Rock Blends were done by using recycled glass at (10, 20, 30, 40, 50)%. The changes in the properties of blends are investigated by using an extensive suite of geotechnical engineering laboratory tests including basic classification tests along with modified compaction, California Bearing Ratio and Los Angeles abrasion tests. The main outcome of this research is the possibility of using recycled glass (4.75 mm maximum particle size) glass in pavement base- class 3 at optimum content is until 30%, which obtained the physical and mechanical properties are good and within the limits of the international standards ASTM.